Concentrations of transition metals in zoobenthos of a gas-hydrate seep near Paramushir Island. - Kuznetsov, Alexey P; Lukashin, Vyacheslav N; Shmelev, Igor P (PANGAEA, 1989)
Bioaccumulation of metals by zoobenthos was investigated during cruise 11A of R/V Akademik Mstislav Keldysh in the vicinity of a gas-hydrate seep off Paramushir Island in the Sea of Okhotsk. Atomic absorption studies of concentrations of Al, Fe, Mn, Ni, Cu and Zn in zoobenthos (polychaetes, bivalves, ophiurans and echinoderms) collected from depths of 700-800 m indicated that their concentrations in individuals near the seep were not significantly different from those in individuals from other communities. Obtained results indicate that sea urchins and holothurians (non-sorting bottom-feeders) can separate mineral fraction of ingested bottom material.
Chemical composition of zoobenthos and bottom sediments from the gas-hydrate seep area near the Paramushir Island, Kuril Island arc
Keywords: AMK11A-1391; AMK11A-1391/5; AMK11A-1400; AMK11A-1401; AMK11A-1401-1; AMK11A-1413; AMK11A-1418; Archive of Ocean Data; ARCOD; MULT; SIGSBY; Sigsby trawl